Analisis Faktor-faktor Yang Mempengaruhi Keputusan Pembelian Produk Skincare MS GLOW Pada Toko MS GLOW Kendy - Sinurat, Eka Sartika; Amalia, Alfi (Universitas Labuhanbatu, 2023)
This study aims to determine the price that influences consumer decisions in buying SkinCare MS Glow products at the MS Glow Kendy Store, to determine product quality that can influence the decision to purchase SkinCare MS Glow at the MS Glow Kendy Store, to determine price and product quality together with the decision purchase of SkinCar MS Glow at the MS Glow Kendy Shop. Researchers used 30 respondents, with the research method used is the Quantitative method. With research data data validity test , reliability test , classical assumption test , multiple linear regression analysis , and hypothesis testing. Price has no effect on the purchasing decision of MS Glow Kendy. This is evidenced by the results of the t test which obtained a sig value for the product quality variable of 0.112 <0.05 (sig < Î± = 5%) so that H0 is accepted. So it can be concluded that the price has no significant effect on the purchasing decision of MS Glow Kendy. Product quality influences the purchasing decision of MS Glow Kendy. This is evidenced by the results of the t test which obtained a sig value for the product quality variable of 0.000 <0.05 (sig < Î± = 5%) so that H0 was rejected. So it can be concluded that product quality has a significant effect on purchasing decisions for MS Glow Kendy.